Implementation Of One Indonesian Data for An Integrated Official Statistical System - Maulana, Alfarizi Rehan (Educational Studies and Research Journal, 2024)
The necessity of each institution in meeting its data requirements raises uncertainties in data governance. Various data versions of the same object create doubts about selecting valid data. Consequently, Presidential Regulation No. 39 of 2019 concerning One Data Indonesia (SDI) was issued, emphasizing the coordination and collaboration of ministries and institutions with other statistical producers, including the Central Statistics Agency, to generate data. This aims to prevent data duplication, ensuring a singular, complete, and valid dataset. Therefore, this study seeks to elucidate SDI and its outcomes in a region that has implemented SDI. The research methodology involves a literature review drawing from various sources on SDI. The study concludes that the implementation of the One Data Indonesia system is crucial to prevent data duplication and enable centralized integration, thereby enhancing data governance quality.